ANALISIS PENGARUH RASIO LIKUIDITAS, LEVERAGE, AKTIVITAS, DAN PROFITABILITAS TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN MAKANAN DAN MINUMAN DENGAN KATEGORI INDUSTRI BARANG KONSUMSI DI BEJ) - ULUPUI, I G. K. A. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 1 (2007), 2007)
The purpose of this study is to empirically study the effect of accounting variables—liquidity ratio, leverage, activity ratio, and profitability ratio—on stock returns of the food and beverage firms registered between 1999--2005 on Jakarta Stock Exchange (JSX). The data is sampled using purposive sample judgment method. From 21 firms registered on JSX only 13 are used as samples for this study. The firms included are Asia Inti Sarana, Ades Alfindo Putra Setia, Aqua Golden Mississipi, Davomas Abadi, Mayora Indah, Indofood Sukses Makmur, Ultra Jaya Milk, Sinar Mas Agro Resources and Technology, Sari Husada , Cahaya Kalbar, Delta Djakarta, Fast Food Indonesia and Tunas Baru Lampung. The result of this study using multiple regression finds that only two variables (return on asset and current ratio) that significantly affect the following year stock return with level of significance 5 percent.
Keywords: financial statements, financial ratio, stock return